DETERMINANTS OF GOVERNMENT OWNERSHIP, POLITICAL CONNECTIONS, PROFITABILITY, AND LEVERAGE ON SUSTAINABILITY REPORTING QUALITY IN PUBLIC COMPANIES IN INDONESIA - Siti Asiah Murni; James Tumewu; Akhmad Zainuddin (RADJA PUBLIKA, 2026)
This study aims to examine the effects of government ownership, political connections, profitability, and leverage on the quality of sustainability reporting in public companies in Indonesia, as well as the moderating role of firm size. Sustainability reporting serves as a crucial tool for companies to demonstrate transparency, accountability, and commitment to environmental, social, and governance (ESG) practices. The research adopts a quantitative approach with a causal-comparative design, and data were collected from 100 publicly listed companies on the Indonesia Stock Exchange (IDX) for the period 2020–2024 using purposive sampling. Secondary data were obtained from annual reports, sustainability reports, ESG databases, and company profiles. The results of multiple linear regression analysis show that government ownership and profitability have a significant positive effect on sustainability reporting quality, indicating that state-owned and financially strong companies are more motivated to produce transparent and comprehensive ESG disclosures. Conversely, political connections have a significant negative effect, suggesting that politically affiliated companies reduce transparency to minimize political risk exposure. Meanwhile, leverage does not have a significant effect, implying that debt levels are not a primary determinant of sustainability reporting quality in the Indonesian context. Furthermore, moderation analysis using PLS-SEM demonstrates that firm size strengthens the relationship between profitability and sustainability reporting quality. Large and profitable companies are more likely to prepare comprehensive sustainability reports due to greater resources and higher stakeholder pressures compared to smaller firms. This study contributes to the literature by integrating political, ownership, financial, and organizational factors in explaining sustainability reporting quality. The findings provide practical implications for regulators, investors, and corporate managers in designing effective ESG disclosure strategies and promoting transparency and accountability in public companies.